System thinking applied to near misses: a review of industry-wide near miss reporting systems. (2nd November 2018) - Thoroman, Brian; Goode, Natassia; Salmon, Paul
Abstract: Learning from near misses is an important component of maintaining safe work systems. Within safety science it is widely accepted that a systems approach is the most appropriate for analysing incidents in sociotechnical systems. The aim of this article is to determine whether industry-level near miss reporting systems are consistent with systems thinking. Twenty systems were identified, from a range of work domains, and were evaluated against systems thinking-based criteria. While none of the reporting systems fulfilled the full set of criteria, all are able to identify actors and contributing factors proximal to events in sociotechnical systems and many capture information on how accidents were prevented. It is concluded that the explanatory power of near miss reporting systems is limited by the systems currently used to gather data. The article closes by outlining a research agenda designed to ensure that near miss reporting systems can fully align with the systems approach.